Measuring flexibility: A text-mining approach - Grajzel, Katalin; Acar, Selcuk; Dumas, Denis; Organisciak, Peter; Berthiaume, Kelly (Frontiers in Psychology, 2023)
In creativity research, ideational flexibility, the ability to generate ideas by shifting between ideas, has long been the focus of investigation. However, psychometric work to develop measurement procedures for flexibility has generally lagged behind other creativity-relevant constructs such as fluency and originality. Here, we build from extant research to theoretically posit, and then empirically validate, a text-mining based method for measuring flexibility in verbal divergent thinking (DT) responses. The empirical validation of this method is accomplished in two studies. In the first study, we use the verbal form of the Torrance Test of Creative Thinking (TTCT) to demonstrate that our novel flexibility scoring method strongly and positively correlates with traditionally used TTCT flexibility scores. In the second study, we conduct a confirmatory factor analysis using the Alternate Uses Task to show reliability and construct validity of our text-mining based flexibility scoring. In addition, we also examine the relationship between personality facets and flexibility of ideas.